Speciation of poultry Eimeria by morphometry and SCAR PCR in Southern India - P, Venkateswara Rao; Raman, M; Dhinakarraj, G; Basith, S Abdul; Gomathinayagam, G (The Indian Journal of Animal Sciences, 2012)
The percentage prevalence of Eimeria tenella, E. maxima, E. acervulina, E. mitis, E. necatrix and E. brunetti were 48.48, 42.42, 12.12, 9.09, 9.09 and 21.21%, respectively, based on morphometric observations. An overall prevalence of different species of Eimeria was recorded as 57.57% in various agroclimatic zones of southern India. Of the 21 samples collected from broiler farms, 13 samples were positive (61.9%) for either single or mixed infection of Eimeria species. Of the 12 samples collected from layer farms, 6 samples (50%) were positive for either single or mixed infection of Eimeria species. PCR using SCAR (sequence characterized amplified region) primers showed amplicons of sizes 811 bp (E. acervulina), 539 bp (E. tenella), 460 bp (E. mitis), 272 bp (E. maxima) and 200 bp (E. necatrix) and their percentage prevalence were 6.06, 27.27, 6.06, 15.15 and 3.03%, respectively.